Multi-phase flow simulation of CO2 leakage through a fractured caprock in response to mitigation strategies. (January 2016) - Vialle, Stéphanie; Druhan, Jennifer L.; Maher, Katharine
Highlights: Flow and transport simulations of CO2 leakage using TOUGH2. CO2 leakage and mitigation through a fractured caprock. Multiple permeability fields evaluated using a grid-based continuum model. Mineral precipitation can lead to lateral migration of the leak. Strategies of controlled permeability reduction may significantly reduce the leak. Abstract: To evaluate the effectiveness of several mitigation strategies, we developed two-dimensional flow and transport simulations of carbon dioxide (CO2 ) leakage through the fractured caprock of a storage reservoir, over timescales of 2–10 years. The fractured system was modeled as a low-permeability fault core surrounded by a fractured damage zone, as would be expected for a low-porosity caprock that underwent brittle deformation. To represent the damage zone, we introduced heterogeneities in the initial permeability field by using a grid-based continuum model where the upscaling relationship for permeability as a function of fracture aperture and density is given by an analytical expression. The first mitigation strategy, injection of a drying agent (dry CO2 here) below the damage zone, leads to precipitation of solids and local decreases in permeability that cause lateral migration of the leak and self-sealing of the fractured system. The higher the maximum value of the permeability in the damage zone, the less time required to reduce the leak rate. The second mitigation strategy evaluated controlled permeability reduction in the fractured zone by simulating an idealized emplaced sealant. Collectively, modeling results suggest that knowledge of the hydrodynamics of the leak is required to optimize the location of sealant applications within the fracture zone.